2009
DOI: 10.4028/www.scientific.net/kem.423.47
|View full text |Cite
|
Sign up to set email alerts
|

Wear Resistance of Metal Oxide Sol-Gel Coatings Deposited over Ceramic Glazes

Abstract: This paper analyse the wear resistance of high reflective metal oxide films of TiO2 (anatase), Fe2O3 (hematite), ZrO2 (Zirconia) and SnO2 (Casiterite) deposited by screen printing over a conventional ceramic glaze (molar composition 0,2CaO.0,15ZnO.0,05K2O.0,1Al2O3 0,45SiO2.0,05ZrO2). All oxide coatings increase the gloss of the substrate producing a lustre effect. Anatase films stand out for their high gloss valour and low roughness Ra. Likewise, all lustres improve the wear resistance of the glaze substrate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…1) [IS] of the coating compared to that of the glaze (1.54-1.56) [2] as it is also reported elsewhere [2,11] that reflectivity (gloss) of glass/glaze surfaces can be increased simply by covering its surface with a single layer of metal oxide having a higher refractive index than that of glass.…”
Section: A Sol Preparation and Sample Preparationmentioning
confidence: 63%
See 1 more Smart Citation
“…1) [IS] of the coating compared to that of the glaze (1.54-1.56) [2] as it is also reported elsewhere [2,11] that reflectivity (gloss) of glass/glaze surfaces can be increased simply by covering its surface with a single layer of metal oxide having a higher refractive index than that of glass.…”
Section: A Sol Preparation and Sample Preparationmentioning
confidence: 63%
“…Hence, the films are widely used in optical coatings with high gloss [2], heat resistant materials [3], optical filters [4], sensors [5], fuel cells [6] and so on. It is reported that hydrophobic and anti-wear properties on table ware can be developed by application of zirconia coatings [7] by sol-gel method and the same coating was developed by inductively coupled oxygen plasma sputtering [8] on ceramic surfaces such as china and porcelain and reported the development of contact angle of water as 90' in [7].…”
Section: Introductionmentioning
confidence: 99%
“…Further, high gloss of the coated substrate can be attributed to the high refractive index (RI) of TiO 2 and Fe 2 O 3 23 in comparison to the normal zircon opacified glaze (1.54) as it is reported that reflectivity of glaze can be increased by applying a layer of oxide having high RI than that of glaze. 6,24,25 The increase in gloss of coated tile enhances its aesthetic appeal and thus could result in high demand in the market. Images of paper weight on uncoated and coated substrates cured at 700 o C are shown in Figs.…”
Section: Energy (Kev)mentioning
confidence: 99%
“…1 Recently, a lot of investigations have been carried out on glazed ceramic tiles to improve its surface functional properties such as soiling, cleanability, wear resistance, gloss and antibacterial property in addition to the above mentioned properties by applying additional coating on the glazed surfaces. [2][3][4][5][6] Coating with a specific or multiple functional properties is applied on glazed surfaces according to the need as these tiles are exposed to different types of environment. In hospitals and bathrooms, antibacterial property is required prior to other properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation